An approach for mechanical property optimization of fused deposition modeling with polylactic acid via design of experiments. Issue 2 (21st March 2016) - Torres, Jonathan; Cole, Matthew; Owji, Allen; DeMastry, Zachary; Gordon, Ali P.
Abstract : Purpose: This paper aims to present the influences of several production variables on the mechanical properties of specimens manufactured using fused deposition modeling (FDM) with polylactic acid (PLA) as a media and relate the practical and experimental implications of these as related to stiffness, strength, ductility and generalized loading. Design/methodology/approach: A two-factor-level Taguchi test matrix was defined to allow streamlined mechanical testing of several different fabrication settings using a reduced array of experiments. Specimens were manufactured and tested according to ASTM E8/D638 and E399/D5045 standards for tensile and fracture testing. After initial analysis of mechanical properties derived from mechanical tests, analysis of variance was used to infer optimized production variables for general use and for application/load-specific instances. Findings: Production variables are determined to yield optimized mechanical properties under tensile and fracture-type loading as related to orientation of loading and fabrication. Practical implications: The relation of production variables and their interactions and the manner in which they influence mechanical properties provide insight to the feasibility of using FDM for rapid manufacturing of components for experimental, commercial or consumer-level use. Originality/value: This paper is the first report of research on the characterization of the mechanical properties of PLA coupons manufactured using FDM by the Taguchi method. The investigation is relevant both in commercial and consumer-level aspects, given both the currently increasing utilization of 3D printers for component production and the viability of PLA as a renewable, biocompatible material for use in structural applications.